Developing The Teaching Of Listening Skills Using An Integrated Listening Method Based On The constructivist Approach And The Communicative Approach - Sarah Munira; Intan Afriati; Syarifuddin Syarifuddin (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2024)
Learning listening skills still leaves many problems. Among them are problems related to students' limbs, thinking, the application of learning methods, media, teacher and so on. Learning process of listening at Ruhul Islam Anak Bangsa Islamic Boarding School tends to be passive where the teacher provides istima' material to students through a laptop and loudspeaker and the teacher gives students questions directly without explaining the previous material and providing opportunities for students to discuss and ask things that are not understood. In addition, the listening learning process tends to be boring and uninteresting. Therefore, researchers developed listening skills learning with the integrative listening method to improve students' listening skills. The purpose of this study was to find out how to develop and effectiveness of the developing listening skills learning using the integrative listening method and to find out students' responses to the development of listening skills learning with the integrative listening method. The method used in this research is a research and development method. The results show that learning listening skills using the integrative listening method developed using the Borg and Gall model. Teaching listening skills with the integrative listening method is effective to increasing students' listening skills. Student responses to learning listening skills using the integrative listening method is very good with the positive answer of 92.67%.